2020
DOI: 10.3847/1538-4357/ab9081
|View full text |Cite
|
Sign up to set email alerts
|

EvryFlare. II. Rotation Periods of the Cool Flare Stars in TESS across Half the Southern Sky

Abstract: We measure rotation periods and sinusoidal amplitudes in Evryscope light curves for 122 two-minute K5-M4 TESS targets selected for strong flaring. The Evryscope array of telescopes has observed all bright nearby stars in the south, producing 2-minute cadence light curves since 2016. Long-term, high-cadence observations of rotating flare stars probe the complex relationship between stellar rotation, starspots, and superflares. We detect periods from 0.3487 to 104 days and observe amplitudes from 0.008 to 0.216 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…This can be explained by us overestimating the spot temperature in equation (5). Our magnetic field results agree with those of Howard et al (2020b), who performed the same analysis using the EvryScope flare sample for cool stars. Our results are also consistent with previous observations of kilogauss magnetic field strengths for K and M stars (e.g.…”
Section: Flares and Star-spot Sizesupporting
confidence: 86%
“…This can be explained by us overestimating the spot temperature in equation (5). Our magnetic field results agree with those of Howard et al (2020b), who performed the same analysis using the EvryScope flare sample for cool stars. Our results are also consistent with previous observations of kilogauss magnetic field strengths for K and M stars (e.g.…”
Section: Flares and Star-spot Sizesupporting
confidence: 86%
“…For example, TESS data for Proxima Centauri (Vida et al 2019) indicate that with spot areal coverage of 5 per cent or more, the observed flare energies can be powered by fields in the range 1-2 kG. And data from EVRYSCOPE (Howard et al 2019) also indicate that flares on stars with spectral types ranging from K7 to M4 have energies such that, with spot areal coverages of at least 4-5 per cent, the most energetic flares can be powered by magnetic fields with strengths of 1.5 kG.…”
Section: R E S U Lt Smentioning
confidence: 99%
“…The flaring properties of these M-dwarfs have been extensively studied at 2 min cadence as part of the EvryFlare Survey (e.g. Howard et al 2018Howard et al , 2019Howard et al , 2020a). The sample is composed of very nearby (23 +27 −12 pc) and bright (g =12.3 +1.4 −1.0 ) flare stars, where the quoted spreads are 1σ standard deviations.…”
Section: Tess Observationsmentioning
confidence: 99%
“…Wakeford et al 2019;Teske et al 2020). Spectral types are updated from those of Howard et al (2020a) with SIMBAD (Wenger et al 2000) classifications where available. Flare stars were selected to cross the fullyconvective boundary with 146 M-dwarfs of types ≈M0-M3, 47 ∼M4 dwarfs, and 16 M5-M6 dwarfs.…”
Section: Tess Observationsmentioning
confidence: 99%